The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/978-3-540-30135-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Texture Image Analysis for Osteoporosis Detection with Morphological Tools

Abstract: Abstract. Osteoporosis is due to the following two phenomena: a reduction bone mass and a degradation of the microarchitecture of bone tissue. In this paper, we propose a method for extracting morphological information enabling the description of bone structure from radiological images of the calcaneus. Our main contribution relies on the fact that we provide bone descriptors close to classical 3D-morphological bone parameters. The first step of the proposed method consists in extracting the grey-scale skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Concerning the characterization of bone microarchitecture, studies has shown that bone changes from a healthy person to a person with osteoporosis [4] or osteoarthritis [3]. These changes are quantified using morphometric parameters of bone microarchitecture such as the number of pixels of the skeleton, the halfwidth and the length of trabeculae, the number of trabeculae and the number of nodes and ends.…”
Section: Skeleton Features In Medical Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the characterization of bone microarchitecture, studies has shown that bone changes from a healthy person to a person with osteoporosis [4] or osteoarthritis [3]. These changes are quantified using morphometric parameters of bone microarchitecture such as the number of pixels of the skeleton, the halfwidth and the length of trabeculae, the number of trabeculae and the number of nodes and ends.…”
Section: Skeleton Features In Medical Imagingmentioning
confidence: 99%
“…Skeletonization is used in various applications such as biometrics [1,2], medical imaging [3,4,5] and character recognition [6] since it provides features that enables user to access high-level analysis of the image objects. In fact, object matching methods based on skeleton features are used in biometric identification through minutiae comparison of hand vein [1] or digital fingerprint [2], in bronchial airway trees monitoring [5], in symbols identification [7] and in character recognition [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foreground is obtained by a thresholding step [1]: we compare the original image (in this case a calcaneum image, figure 1(a)) to its local ppercentile computed on a sliding window of size w. Then two thinning methods are proposed: a classical binary skeletonization and a grey thinning close to the Mersal algorithm [2]. The latter consists in two steps.…”
Section: Medical Image Analysis To Detect Osteoporosismentioning
confidence: 99%
“…The most challenging task is to characterize bone micro architecture by parameters that can be automatically estimated from images and that can accurately detect and quantify alterations of bones. For this, we have developed an original approach using morphological tools to extract characteristic features of trabecular bone images [1]. To make such an approach operational for medical diagnosis, it is necessary to determine an "image protocol" adapted to bone types (e.g.…”
Section: Introductionmentioning
confidence: 99%